2017
DOI: 10.1038/s41598-017-10050-5
|View full text |Cite
|
Sign up to set email alerts
|

In vivo photothermal optical coherence tomography of endogenous and exogenous contrast agents in the eye

Abstract: Optical coherence tomography (OCT) has become a standard-of-care in retinal imaging. OCT allows non-invasive imaging of the tissue structure but lacks specificity to contrast agents that could be used for in vivo molecular imaging. Photothermal OCT (PT-OCT) is a functional OCT-based technique that has been developed to detect absorbers in a sample. We demonstrate in vivo PT-OCT in the eye for the first time on both endogenous (melanin) and exogenous (gold nanorods) absorbers. Pigmented mice and albino mice (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 56 publications
1
45
0
Order By: Relevance
“…In the past, PT-OCT of melanin in the eye had only been tested by comparing WT mice to albino mice imaged during separate experiments. 28 Thus, the current study provided a more robust validation of PT-OCT sensitivity to melanin within a single retina. We further demonstrated that the PT-OCT signal for pigmented ROIs increases linearly with laser power, as predicted by theory.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In the past, PT-OCT of melanin in the eye had only been tested by comparing WT mice to albino mice imaged during separate experiments. 28 Thus, the current study provided a more robust validation of PT-OCT sensitivity to melanin within a single retina. We further demonstrated that the PT-OCT signal for pigmented ROIs increases linearly with laser power, as predicted by theory.…”
Section: Discussionmentioning
confidence: 85%
“…PT-OCT is a functional OCT technique that detects optical absorbers such as gold nanoparticles 25 or indocyanine green 35 and has recently been demonstrated in the eye for the first time. 28 In this study, we used PT-OCT to image the distribution of melanin in the zebrafish retina. Melanin is naturally present in the RPE, and changes in retinal pigmentation are observed in multiple eye conditions, such as AMD, 6 albinism, 36 and retinitis pigmentosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Photothermal OCT (PTOCT) is another functional extension of OCT, based on the photothermal effect, which enables the detection of the optical absorbers in tissues. By taking advantage of the strong absorption in IR by melanin, Lapierre-Landry et al 23,24 demonstrated the capability of PTOCT to image melanin distribution in mice and zebrafish retina, and the migration of melanin within RPE in response to dark and light adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…fluorescent markers), which enable localization of cell types, patterns of protein expression, and imaging of lymph/blood vessels 2 . The majority of previous work has focused on use of a single contrast agent, such as absorptive dyes 3 , microbeads 4,5,6 , and gold nanoparticles 7,8,9 . Two-plex imaging of gold nanoparticles has been demonstrated, but only under the assumption that each voxel contained a single type of contrast agent 10,11 .…”
mentioning
confidence: 99%